Prevalence of CYP2C19 Gene Polymorphism and Its Influence In Omeprazole Metabolism As Predictors Of Drug Inoxification In Malay Ethnic In South Sumatra: Prevalensi Polimorfisme Gen CYP2C19 dan Pengaruhnya Dalam Metabolisme Omeprazole Sebagai Prediktor Intoksikasi Obat Pada Etnis Melayu Di Sumatera Selatan - Triwani, Triwani; Hayati, Lusia (Fakultas Kedokteran Universitas Sriwijaya, 2018)
Cytochrome P450 2C19 (CYP2C19) is an enzyme complex that plays a role in the metabolism of several drugs and is part of the super family of cytochrome P450. Genetic polymorphisms in these enzymes are associated with the emergence of poor metabolic phenotypes (poor metabolizers / PMs and intermediate metabolizers / IMs) that have a poor ability to metabolize the drugs that become substrates. Genotypes and phenotypes were analyzed using PCR-RFLP and bio-analysis of omeprazole levels in 30 subjects from ethnic Malay living in South Sumatra. Markers used to assess the presence of polymorphisms in the CYP2C19 gene are two polymorphic sites of exon 5 (CYP2C19 * 2) and exon 4 (CYP2C19 * 3). 321 bp DNA bands for exon 5 and 271 bp for exon 4 will be produced after DNA amplification by PCR method under denaturation for 5 min at 95oC; followed by 60 seconds at 95oC, 60sec at 53oC and 60sec at 72oC for 30 cycles; as well as the final polymerization for 5 minutes at 72 Â° C. Furthermore, DNA cutting was done using the restriction enzyme endonuclease SmaI (CYP2C19 * 2) at 30oC and BamHI (CYP2C19 * 3) with incubation at 37oC for 3 hours. Bioanalysis of omeprazole levels in the blood with LC-MS. The results of this study indicate the presence of polymorphisms on both sites will eliminate the enzyme sites SmaI and BamHI. The results showed that 46.7% of South Sumatran Malay populations were classified as PM consisting of 13.3% homozygous mutandan mutant 33.4% heterozygotes. The high phenotype of PM enzyme CYP2C19 in ethnic Malays in South Sumatra predicted to influence metabolism of drugs become substrates. However, based on spearman correlation analysis, the correlation value was 0.035 with p = 0.875. This means that between the CYP2C19 gene polymorphism and the omeprazole levels in the blood there is a weak and meaningless correlation. The results of this study provide an overview of the high genetic polymorphisms of dyspepsia syndrome patients from the Malay population, ie almost half of the study subjects (46.7%). There is a weak and insignificant correlation between polymorphism and omeprazole levels.